Experiences of staff nurses in implementing patient identification: a phenomenological study at Tzu Chi Hospital - Afrinda Rahmawati; Sri Oktri Hastuti; Arimbi Karunia Estri (International Journal of Health Science and Technology, 2026)
Accurate patient identification is a key component of patient safety efforts aimed at preventing medical errors and medication errors. This qualitative phenomenological study aimed to explore the experiences of practicing nurses in implementing accurate patient identification in the inpatient ward at Tzu Chi Hospital. The participants consisted of 10 practicing nurses selected through purposive sampling. Data were collected through in-depth interviews and direct observation, then analyzed using thematic analysis. The results showed that nurses had a good understanding of the importance of patient identification. Verification practices included checking wristbands, confirming names and dates of birth, scanning barcodes, and performing double-checks. However, barriers were identified, such as high workload, uncooperative pediatric patients (bracelets coming off), and familiarity bias. Patient safety practices were also supported by SBAR communication, fall prevention, and infection control. The study’s conclusion emphasizes that although nurses’ knowledge is excellent, practical compliance in the field is not yet fully consistent due to contextual barriers related to pediatric patients and workload. Therefore, it is recommended to strengthen adaptive pediatric identification systems, provide periodic training (nursing sharing), conduct routine supervision, and foster a no-blame culture for incident reporting to ensure optimal and sustainable implementation of patient safety.